Analisis Dampak The Dark Triad Terhadap Perilaku Kerja Karyawan Generasi Z di Lingkungan Organisasi Modern - Aulia Silvana; Amelia Rahmadani; Naura Rahadhatul Aisy; Tariza Mega Pratiwi Garini; Sofa Parihah Nurasiah (Indo Publishing, 2026)
The dynamic organizational environment requires companies to understand the factors influencing employees' work behavior, including personality traits associated with The Dark Triad, namely Machiavellianism, narcissism, and psychopathy. This study aims to analyze the influence of Dark Triad characteristics on the work behavior of Generation Z employees in modern organizational settings. The study employs a Systematic Literature Review (SLR) using a descriptive approach through the identification, selection, and synthesis of relevant scientific literature. The findings indicate that Dark Triad characteristics are associated with higher levels of Counterproductive Work Behavior (CWB), poorer interpersonal relationships, workplace ostracism, and unethical behavior in the workplace. Among the three dimensions, Machiavellianism is identified as the most dominant predictor of counterproductive work behavior due to individuals' tendency toward manipulation and self-interest. In addition, Early Maladaptive Schemas contribute to explaining these behavioral tendencies. These findings highlight the importance of considering personality traits in human resource management practices to foster a productive, collaborative, and ethical work environment for Generation Z employees.